1998
DOI: 10.1046/j.1365-313x.1998.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

A general method for gene isolation in tagging approaches: amplification of insertion mutagenised sites (AIMS)

Abstract: SummaryA polymerase chain reaction (PCR) based procedure for the isolation of genes in transposon or T-DNA tagging approaches has been developed. The method can be generally applied and allows the rapid isolation of putative gene sequences even in the presence of high numbers of insertion sequences. The technique has been used successfully for the isolation of the maize Bx1 gene tagged by a Mutator element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 11 publications
0
71
0
Order By: Relevance
“…Additionally, a small population of 24 individuals segregating for the ig1-mum allele was used to test for a cosegregating Mu band using a modified amplification of insertion mutagenized sites protocol (Frey et al, 1998). One band that cosegregated with ig1-mum contained a Mu (Iwakawa et al, 2002;Shuai et al, 2002).…”
Section: Fine Mapping and Cloning Of Ig1mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a small population of 24 individuals segregating for the ig1-mum allele was used to test for a cosegregating Mu band using a modified amplification of insertion mutagenized sites protocol (Frey et al, 1998). One band that cosegregated with ig1-mum contained a Mu (Iwakawa et al, 2002;Shuai et al, 2002).…”
Section: Fine Mapping and Cloning Of Ig1mentioning
confidence: 99%
“…Amplification of insertionmutagenized sites was performed using a protocol modified from that of Frey et al (1998). Approximately 500 ng of DNA was digested per sample with 5 units of HinP1I (New England Biolabs), and then adaptors were ligated overnight using 1 unit of T4 DNA ligase (Fermentas).…”
Section: Cloning Of Ig1mentioning
confidence: 99%
“…Six tightly linked and cosegregating low-copy amplification of insertion mutagenized sites (AIMS) fragments (Frey et al, 1998) were identified from three rf1-m families (Wise et al, 1996) and, along with sequences selected from the cosegregating 6140-1 cDNA (Wise et al, 1999), were used as probes against the first B73 library filters (ZMMBBa; Clemson University Genomics Institute). From each of the resulting short nonoverlapping contigs, overgo probes were designed off sequenced BAC ends.…”
Section: Analysis Of Multiple B73 Maize Bac Libraries Leads To Two Sementioning
confidence: 99%
“…Three maize (Zea mays) rf1-m allele families (rf1-m3207, rf1-m7323, and rf1-m7212; Wise et al, 1996) were analyzed by a modification of the AIMS method (Frey et al, 1998). DNA was extracted from each individual plant of a segregating population.…”
Section: Identification Of Bacs In the Rf1 Regionmentioning
confidence: 99%
“…The sxd1 gene is expressed in bundle sheath cells and is upregulated in maturing leaf blades. Mezitt cloned the sxd1 allele using a protocol for differential display of Mu transposons by amplification of insertion-mutagenized sites (Frey et al, 1998). Mu transposontagging is a popular strategy of mutagenesis in maize, and the continued development of new Mu-cloning procedures promises to augment the existing protocols for gene discovery.…”
Section: Transposon Tagging and Gene Identificationmentioning
confidence: 99%